Ergosterol extraction: a comparison of methodologies - Wilkes, Thomas I. (The Microbiology Society, 2023)
Ergosterol is a component of the cell membrane of mycorrhizal fungi and is frequently used to quantify their biomass. Arbuscular mycorrhizal (AM) fungi and ectomycorrhizal (ECM) fungi establish a symbiotic relationship with a respective host plant. Several methods are currently employed for quantification of ergosterol; however, these utilise a series of potentially hazardous chemicals with varying exposure times to the user. The present comparative study aims to ascertain the most reliable method to extract ergosterol whilst limiting hazard exposure to the user. Chloroform, cyclohexane, methanol and methanol hydroxide extraction protocols were applied to a total of 300 samples of root samples and a further 300 growth substrate samples across all protocols. Extracts were analysed via HPLC methodologies. Chromagraphic analysis showed chloroform-based extraction procedures produced a consistently higher concentration of ergosterol in both root and growth substrate samples. Methanol hydroxide, without the addition of cyclohexane, produced a very low concentration of ergosterol, with a reduction of quantified ergosterol of between 80 and 92 % compared to chloroform extractions. Hazard exposure was greatly reduced following the chloroform extraction protocol when compared with other extraction procedures.
Keywords: chloroform; cyclohexane; ergosterol; fungal biomass; methanol and mycorrhizal fungi